2019
DOI: 10.35940/ijeat.a3052.109119
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous NiO Nanoflower based Humidity Sensor Grown on Seedless Glass Substrate via One Step Simplistic Immersion Method

Abstract: A highly porous nickel oxide (NiO) nanoflower was deposited directly onto glass substrates by the simplistic immersion method. The nanostructural property of the NiO was studied by X-ray diffraction pattern and obtained high crystal quality after annealing at 500 °Ϲ with an average crystallite size of 15.5 nm. The optical characterization was measured by ultraviolet-visible spectroscopy, with an average transmittance of 58 %. The value of 3.63 eV was estimated and confirmed as NiO bandgap energy. The current-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The growth of CR is scattered and not uniform.Both undoped and doped samples have similar nanostructures with no significant differences. This structure is observed as in the previous study, where the same immersion method was used[12]. The only difference between the two samples is their nanosheet and CR thickness.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The growth of CR is scattered and not uniform.Both undoped and doped samples have similar nanostructures with no significant differences. This structure is observed as in the previous study, where the same immersion method was used[12]. The only difference between the two samples is their nanosheet and CR thickness.…”
supporting
confidence: 82%
“…In this study, besides undoped NiO, lithium (Li) is used as a dopant element to be incorporated with NiO. The immersion method is employed to deposit undoped and Li-doped NiO nanostructures, with a NiO thin film (TF) used to enhance the adhesion between the nanostructures and glass substrates, as previous research has confirmed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover,  -Fe2O3 is abundant, nontoxic, low cost, and suitable for use in sensors, catalysts pigments, and anode materials [17,18]. Besides  -Fe2O3, NiO exhibits a broader bandgap, usually reported within 3.6-4.0 eV at room temperature [19,20]. In addition to being considered transparent in the visible light region [21], NiO also possesses good electrical conductivity and a high surface to volume ratio [22].…”
Section: Introductionmentioning
confidence: 99%